UNDERSTANDING THE HADITHS PROHIBITING PERFUME FOR WOMEN: A Hermeneutic Analysis by Nashr Hamid Abu Zayd - Lailiyatun Nafisah; Ach. Jalaluddin Ar Rumi (Riwayah: Jurnal Studi Hadis, 2024)
The use of perfume among Muslim women has sparked debate due to prophetic traditions (hadiths) prohibiting it. This article reexamines the interpretation of these hadiths, which, when understood literally, contradict contemporary contexts. Initially associated with negative connotations, perfume has evolved into a symbol of self-respect and consideration for others. This qualitative study employs a literature-based research design, utilizing primary sources from hadith collections and secondary sources from books, journals, and related research. The study aims to reevaluate the prohibition's meaning within relevant contexts. Nashr Hamid' Abu Zayd's hermeneutics is guided by extracting three principles, namely dalalah, maghza and maskut 'anhu. Applying Nashr Hamid Abu Zayd's hermeneutics, the research reveals that Islamic teachings permit perfume use if it doesn't cause disturbance and promotes environmental comfort. The signification of the hadith is that Islam teaches not to have an excessive attitude, care about environmental cleanliness and respect for others. The dimension of  unrelated dimension is the excessive use of perfume and with the wrong intention, such as flirting with the opposite sex is prohibited. Furthermore, excessive or malicious perfume use, particularly for seduction, is prohibited due to its potential harm and exploitation of women.